Personalized Learning Environment (PLE) : Classification Of Dominant Learning Styles - Shahbodin, Faaizah; Che Ku Mohd, Che Ku Nuraini; Che Pee @ Che Hanapi, Ahmad Naim (AENSI, 2014)
Background: Generally, many people recognize that each person prefers different learning styles and techniques. Learning styles group common ways that people learn. Everyone processes and learns new information in different ways. Some people may find that they have a dominant style of learning, with far less use of the other styles. Objective:The aim of the study was to classify the dominant learning styles among Form 2 student of secondary school in Malacca,Malaysia. There are three types’ of dominant learning styles which is Visual, Auditory and Kinesthetic.Results: The results revealed the classification of dominant students’ learning styles. The study also can provide useful information for improving the quality of the teaching and learning experiences of students. Conclusion: Therefore,the students' learning style preference is important for a high quality, effective teaching and learning process.